FAKTOR - FAKTOR YANG MEMPENG ARUHI CASH HO LDING PADA PERUSAHAAN KO NS UMEN NON-PRIMER - Noreen, Keisha; Sufiyati, Sufiyati (Jurnal Paradigma Akuntansi, 2025)
The point for this research is identify and analyze the impact of firm size, net working capital, leverage, and revenue growth on cash holdings. The resea rch methodology used was a targeted sa mple of the entire sample of 61 cyclical comp a nies list e d on th e Indonesian Sto ck Exchange (IDX). T his study was conduct ed usi ng observatiion years 2018-2021. The type of this data is used seconddary da ta and its taken fro m financial reports on www.idx.com. The results of this study show that firm size not impact and positive on cash holdings, while net working capital and leverage impact and negative on cash holdings and growth has no impact and negative on cash holdings.